Impacto do trabalho noturno na qualidade de vida do profissional de enfermagem do gênero masculino - Aquino, Rafael Lemes de (2016)
The nursing staff is now the largest contingent of professionals in healthcare environments, with more than 1.8 million professionals, and of these 15% are men, showing a masculinization of the historical profession and culturally conceived and carried out by women (COFEN / FIOCRUZ, 2013). This dissertation discusses the profession forward to some issues related to gender, quality of life and night work. Objective: To analyze the impact that shift work has the professional quality of life male, through a specific instrument to identify the main problems and joint damage to that front group to his professional activity. Methods: descriptivo, Cross-sectional study with a quantitative approach, performed with 72 professional male nursing staff, 41 (56.9%) nursing technicians, 18 (25%) of nursing assistants and 13 (18.1%) of nurses, in January 2015 in a university hospital in the city of Uberlândia (Minas Gerais). For this, we used the WHOQOL-BREF questionnaire. Quantitative variables were described as mean, standard deviation, maximum and minimum, in addition to the Shapiro-Wilk test and Kruskal-Wallis used in the data analysis, with a confidence level of 5% (p <0.05). Results: the profile of respondents, most are married 42 (58.3%) under the employment contract via Single Legal Regime 50 (69.4%) with mean age of 40 and having 16 years of service; and within a range of 0 to 100, the areas with better evaluation were the Social Relations (70.1) and psychological (67.5); already the worst were the Environment (57.4) and Physical (65.4). In the overall assessment, the average was 63.3 and staying below the national average (65-70). Thus, the professionals who were married obtained better scores, regardless of the category which is in the nursing team. Conclusions: The group is average, taking into account the standard deviation, but we can say that working conditions affect their profession, and these results allow the detection of the difficulties experienced by men of the nursing team, and can cooperate with the design strategies that benefit or minimize the search for conflicts that affect the health of these workers and their quality of life.